Radiomics and radiogenomics in intrahepatic cholangiocarcinoma - A. D. Smirnova; G. G. Karmazanovsky; E. V. Kondratyev; N. A. Karelskaya; V. N. Galkin; A. Yu. Popov; B. N. Gurmikov; D. V. Kalinin (Исследования и практика в медицине)
Purpose of the study. Analytical review and analysis of available literature on texture analysis of computed tomgraphy (CT) and magnetic resonance imaging (MRI) in noninvasive diagnosis of ICC and correlation with molecular genetic features and tumor immunophenotype.Materials and methods. The scientific publications and clinical guidelines in the information- analytical systems PubMed, Scopus for 2012–2022 were carried out using the keywords: "mri", "radiomics", "texture analysis", "radiogenomics", "intrahepatic cholangiocarcinoma", "molecular". 49 articles were selected for analysis after excluding studies dealing with technical aspects of radiomics and describing individual clinical observations.Results. The presented review demonstrated the broad possibilities and prospects of application of CT and MRI texture analysis in the study of cholangiocellular cancer, including the first results in the study of molecular features (signatures) of this tumor. Correlation of texture features with the expression of immunotherapy target genes KRAS/NRAS/BRAF as well as IDH1/2 mutation was shown. Texture scores were the predominant independent predictor of microvascular invasion, which was a major independent risk factor for postoperative recurrence.Conclusion. The use of texture analysis undoubtedly demonstrates promising possibilities both in noninvasive assessment of the HCC histological differentiation grade, as well as in differential diagnosis with hepatocellular carcinoma, metastases, and requires further study for systematization and standardization of the obtained data.